Optimising roadheader performance based on laboratory and field work - Gollick, Michael John (1999)
This thesis covers in detail a study of the excavation of rock salt by roadheader, the factors affecting performance and finally a specification with operational results of a new production machine to suit the South African Coal Mining Industry.